BOARDING SCHOOL SEBAGAI SOLUSI PENGUATAN PENDIDIKAN RELIGIUS SISWA - Al Fikri, Muhammad Dhiyaulhaq; Hafidz, Hafidz (PAI RAFAH, 2024)
Strengthening religious education is one of the solutions implemented for female students in the current era, especially for MAN 2 Surakarta female students. Strengthening this education by providing a driving point for education in boarding schools. This boarding school is a school education system in which students, teachers, and school administrators are in the same school environment for a certain period of time. The program provided at MAN 2 provides a form of strengthening religious education in the form of enthusiasm for religion, historical values, ​​and moral wisdom applied in the Islamic religion. By considering various existing local and global changing trends, to provide a form of strengthening religious education MAN 2 Surakarta has opened a recommended solution in the form of a Boarding School which has various objectives such as; Restoring enthusiasm for religion, Raising noble historical values ​​in nationalism and moral wisdom, Carrying out the mandate in realizing quality education in the development of students' potential, Preparing student graduates to master religious sciences in balance with the development of general sciences and current technology. In implementing this, therefore, collaboration and elaboration between religious science and general science and currently developing technology is needed to create harmony and balance which allows both students and teaching staff to provide reinforcement that is not only about faith but also provides Another form of strengthening is in the form of know